2022
DOI: 10.3390/agriculture12091449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conservation Tillage on Soil Properties and Maize Yield in Karst Regions, Southwest China

Abstract: Karst rocky desertification associated with human disturbance is one of the most serious eco-environmental problems, threatening the sustainable development of agriculture in southwestern China. In the current study, the practice of conservation tillage as one of the best ways of reducing the constraints is addressed. During a two-year trial (2014–2015), the effects of no tillage with straw cover (NT) and traditional tillage (TT) on soil properties and maize yields were investigated in karst regions, Southwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…It suggests that Ks and Da were more suitable in TA than CA soil [27,39], and this study obtained similar data (Figures 5 and 6). However, corn grain yield did not significantly differ between CA and TA [63]. On the other hand, corn grain yield [81] and other crops [82] did not increase significantly when lime and dolomite were applied, probably because the reaction time of the liming agents in soil was much longer than in this study.…”
Section: Soil Chemistry Variablescontrasting
confidence: 60%
See 1 more Smart Citation
“…It suggests that Ks and Da were more suitable in TA than CA soil [27,39], and this study obtained similar data (Figures 5 and 6). However, corn grain yield did not significantly differ between CA and TA [63]. On the other hand, corn grain yield [81] and other crops [82] did not increase significantly when lime and dolomite were applied, probably because the reaction time of the liming agents in soil was much longer than in this study.…”
Section: Soil Chemistry Variablescontrasting
confidence: 60%
“…The low value of the TA soil Bd in the first layer could be explained by soil mechanical fracture due to tillage and reduction in soil total porosity [59,61,62] and by low clay content [27]. However, similar studies showed that at the transition beginning from TA to CA, soil Bd was not significantly different [15,29,61,[63][64][65]. In other studies, TA soil Bd was significantly higher than in CA soil, but only in soils with a high clay percentage [27].…”
Section: Bulk Density (Bd)mentioning
confidence: 78%
“…Al-Wazzan and Muhammad [1] found that no-tillage systems considerably lower soil bulk density while raising soil porosity and organic matter in contrast to conventional tillage systems. Similarly, According to Bai et al [2], for conventional tillage and no tillage treatments, the mean soil bulk density in the experimental site in November 2013 was 1.27 g cm −3 , with soil depths ranging from 0 to 30 cm. After a two-year trial with different tillage intensities, there was a little decrease in soil bulk density in the no-till plots with straw cover compared to conventional tillage.…”
Section: Bulk Density and Porositymentioning
confidence: 63%
“…The plight of agricultural production in karst areas has been an important constraint on regional economic development, especially in southwest China (Bai et al, 2022). The fragile ecological environment has led to a severe shortage of arable land, forcing farmers to plant maize on marginal and sloping land (Gao et al, 2022), where severe soil erosion and nutrient leaching usually occur (Herout et al, 2018).…”
mentioning
confidence: 99%
“…For example, many studies have shown that conservation tillage has no or even negative effects on maize yield (Peng et al, 2020;Zhang, K. P., et al, 2022a). In addition, many studies conducted in the karst areas focused only on the impact of tillage practices (Jia et al, 2019;Bai et al, 2022), ignoring the possible interactive effects with other factors, such as precipitation quantity and distribution (Zhang, Q., et al, 2022b), fertilization, crop type, and other agronomic practices (Wang et al, 2018).…”
mentioning
confidence: 99%